Empowerment of Cleaning Service Staff through Organic Waste Composting at the Palu Ministry of Health Polytechnic - Maryam; Indro Subagyo (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2026)
Organic waste management remains a challenge in institutional environments, including higher education settings. At the Palu Ministry of Health Polytechnic, organic waste such as grass clippings and leaf litter is typically discarded or burned, despite its potential to be converted into value-added compost. This community service program aimed to improve the technical skills and entrepreneurial motivation of cleaning service staff in processing organic waste into compost. The program was conducted on November 26, 2025, involving six cleaning service staff and two students. A participatory training approach was implemented through preparation, instructional delivery, hands-on composting practice, and evaluation. A one-group pre-test–post-test design was used to assess effectiveness. The results showed an increase in the average score from 56.25 to 85.00, indicating a 51.1% improvement. All participants were able to independently perform composting, and 75% expressed interest in developing compost-based business activities. The program also contributed to reducing organic waste on campus. In conclusion, the integration of technical training and entrepreneurship effectively enhanced participants’ skills and motivation. Continuous mentoring and institutional support are recommended to ensure sustainability.